2013
DOI: 10.1085/jgp.201210937
|View full text |Cite|
|
Sign up to set email alerts
|

Channel properties of the splicing isoforms of the olfactory calcium-activated chloride channel Anoctamin 2

Abstract: Anoctamin (ANO)2 (or TMEM16B) forms a cell membrane Ca2+-activated Cl− channel that is present in cilia of olfactory receptor neurons, vomeronasal microvilli, and photoreceptor synaptic terminals. Alternative splicing of Ano2 transcripts generates multiple variants with the olfactory variants skipping exon 14 and having alternative splicing of exon 4. In the present study, 5′ rapid amplification of cDNA ends analysis was conducted to characterize the 5′ end of olfactory Ano2 transcripts, which showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
(92 reference statements)
2
39
0
Order By: Relevance
“…, typical of all TMEM16B isoforms (Pifferi et al, 2009aStephan et al, 2009;Ponissery Saidu et al, 2013), but we observed a stationary current similar to the behavior of TMEM16A currents in inside-out patches (Ni et al, 2014;Tien et al, 2014;Yu et al, 2014).…”
Section: +supporting
confidence: 79%
See 1 more Smart Citation
“…, typical of all TMEM16B isoforms (Pifferi et al, 2009aStephan et al, 2009;Ponissery Saidu et al, 2013), but we observed a stationary current similar to the behavior of TMEM16A currents in inside-out patches (Ni et al, 2014;Tien et al, 2014;Yu et al, 2014).…”
Section: +supporting
confidence: 79%
“…It is important to note that splice variants have been identified both for TMEM16A (Caputo et al, 2008;Ferrera et al, 2009Ferrera et al, , 2011 and for TMEM16B (Stephan et al, 2009;Ponissery Saidu et al, 2013), and it has been shown that some functional channel properties such as Ca 2+ sensitivity and time and voltage dependence differ among the various isoforms of each protein (Ferrera et al, 2010;Huang et al, 2012;Pedemonte and Galietta, 2014).…”
Section: +mentioning
confidence: 99%
“…As previously reported [15,16,32], in TMEM16B wt channel the K 1/2 was slightly voltage-dependent ranging from 4.6 ± 0.2 μM at -50 mV to 2.9 ± 0.1 μM at +50 mV ( n = 7; Wilcoxon signed rank test; Fig 6C). Similar results were obtained for K540Q mutant, whereas R573E and R573E+K540Q showed a significant increase of K 1/2 reaching at -50 mV 28 ± 4 μM and 44 ± 15 μM respectively.…”
Section: Resultssupporting
confidence: 86%
“…NP_705817.1). This is the retinal isoform with the same start site of the olfactory isoform used in Stephan et al (2009) and contained exon 14 (Ponissery Saidu et al, 2013; named exon 13 in Stephan et al [2009]). 2 µg cDNA was transfected into HEK 293T cells using FuGENE-6 or X-tremeGENE 9 (Roche).…”
Section: Heterologous Expressionmentioning
confidence: 99%
“…In TMEM16B, some glutamic acids in the first putative intracellular loop contribute to voltage dependence . A recent study identified splice variants for TMEM16B and found that N-terminal sequences affect Ca 2+ sensitivity (Ponissery Saidu et al, 2013).…”
Section: Ionic Solutionsmentioning
confidence: 99%